Vibration control for torsionally irregular buildings by integrated control system. (15th December 2019) - Akyürek, Osman; Suksawang, Nakin; Go, Tiauw Hiong
Highlights: New Integrated Control System (ICS) was developed for torsion irregular building. The ICS is more effective in controlling rotational direction than traditional TMD. The ICS can reduce the potential seismic damage for torsion irregular building. The tuning design of the ICS is adaptable to restrict multi-directions movements. Abstract: Torsion irregularity increases the risk of building failure during a strong dynamic excitation that is generated by earthquakes or wind gusts. To enhance the safety and performance of torsional irregular buildings, a newly developed Integrated Control System (ICS) is proposed in this research. The new control approach was applied to a two-way eccentric Benchmark 9-story steel building, constructed for the SAC steel project in California, where each floor is represented by two translational and one rotational degree of freedom. The performance and effectiveness of the ICS were examined and compared with a Tuned Mass Dampers (TMDs) approach by subjecting the building to real earthquake excitations of N-S and E-W components of El Centro in 1940, Loma Prieta in 1989, and Kocaeli, Turkey in 1999. Results showed that the ICS was effectively mitigating the lateral and coupling vibrations by the new design configuration and arrangement for both tuning and detuning cases. The ICS is also more robust in restricting the inter-story drift ratio as compared with TMDs.